Don’t Pitch Like a Girl!: How Gender Stereotypes Influence Investor Decisions - Balachandra, Lakshmi; Briggs, Tony; Eddleston, Kim; Brush, Candida (Entrepreneurship Theory and Practice, 2019)
We consider the role that gender-stereotyped behaviors play in investors’ evaluations of men- and women-owned ventures. Contrary to research suggesting that investors exhibit bias against women, we find that being a woman entrepreneur does not diminish interest by investors. Rather, our findings reveal that investors are biased against the display of feminine-stereotyped behaviors by entrepreneurs, men and women alike. Our study finds that investor decisions are driven in part by observations of gender-stereotyped behaviors and the implicit associations with the entrepreneur’s business competency, rather than the entrepreneur’s sex.